تعليم القواعد و تعلمها في السنة الأولى من التعليم المتوسط في ضوء المقاربة التواصلية دراسة تحليلية نقدية - طعبلي, مدني, مروة ابتسام (University of El-oued, 2021)
يطرح هذا البحث المعنون ب" تعليم القواعد و تعلمها للسنة الأولى من التعليم المتوسط قضية تعليم القواعد وتعلمها في ضوء المقاربة التواصلية " دراسة تحليلية نقدية". - وهدف هذا البحث، ليس وضع طريقة لتدريس قواعد اللغة العربية في مرحلة التعليم المتوسط بل هو محاولة قيام بدراسة وصفية نقدية تحليلية لواقع تعليم القواعد وتعلمها في الوثائق التربوية والكتاب المدرسي، بالإضافة إلى تسليط الضوء على المقاربة التواصلية وإبراز أهميتها في تعليم القواعد وتعلمها، حيث خلصنا في هذه الدراسة إلى أن الوثائق التربوية الثلاث ،المنهاج، والوثيقة المرافقة، ودليل استعمال الكتاب ، لم تورد مصطلح المقاربة التواصلية بطريقة مباشرة لكن أشارت إلى المقاربة النصية والتي تعد جزءا منها، أما الكتاب المدرسي يعد مصدر للنصوص و التي هي منطلق للنشاط المدرسي This research, entitled "grammar teaching and learning for the first year of intermediate education, raises the issue of grammar teaching and learning in the light of the communicative approach, "a critical analytical study". - The aim of this research is not to develop a method for teaching Arabic grammar in the intermediate education stage, but rather it is an attempt to conduct a descriptive, critical and analytical study of the reality of grammar teaching and learning in educational documents and textbooks, in addition to shedding light on the communicative approach and highlighting its importance in grammar teaching and learning. This study indicates that the three educational documents, the curriculum, the accompanying document, and the book's usage guide, did not directly mention the term communicative approach, but referred to the textual approach, which is part of it, while the textbook is a source of texts that are a starting point for school activity..
Keywords: القواعد، المقاربة التواصلية، المقاربة النصية، المنهاج، الوثيقة المرافقة، دليل الأستاذ، الكتاب المدرسي; Grammar, communicative approach, textual approach, curriculum, accompanying document, teacher's guide, textbook